Crecimiento de plantaciones forestales de Tectona grandis L. f. (TECA) en las plantaciones Colina Forestal, La Vanguardia y Sabana Uno, propiedad del Grupo Siembra en el Cantón Balzar, Provincia del Guayas. - Rosado Martínez, Orlando Gabriel (2017)
The present work had as objective to evaluate the growth of plantations of Tectona grandis L. f., in the plantations Colina Forestal, La Vanguardia and Sabana Uno; owned by the Grupo Siembra in the Balzar canton, Guayas province. In order to carry out the research, volume, diameter and total height data were taken from randomly distributed PPMs, seven rectangular plots were evaluated in each locality of 768 m2. Measures for the years 2015, 2016 and 2017 were taken into account, forestry plantations were established in 2011, metrics, hypsometer and GPS were used for measurements. The results obtained were as follows; in the general average of the three evaluation periods Sabana Uno obtained better volume with 25,34 m3 and an IMA of 4,22 m3; the general average of the diameter also Sabana Uno presented better results with 8.73 cm and an IMA of 1,46 cm; in height, the highest averages were in Colina Forestal with 9,09 m and an IMA of 1,52 m. The analysis of variance of the general average for the variables measured with the respective Tukey test with 95% confidence, shows that there is no significant difference in the evaluated localities, in conclusion there are no big differences in the growth of the teak plantations of the Grupo Siembra.